Biochar and Compost Application of Livestock on The Growth and Results of Red Chili Plants - Siska Damayanti; Yohanes Parlindungan Situmeang; Anak Agung Ngurah Mayun Wirajaya (Warmadewa University Press, 2020)
Abstract This study aims to determine the effect of compost and biochar made from livestock manure and its interaction on the growth and yield of red chili plants. in former farmers' rice fields in Blahkiuh Village, Abiansemal District, Badung Regency, with an altitude of about 400-500 meters above sea level. This research activity took place from March to July 2020. The design used in this study was a factorial randomized block design (RBD) consisting of 2 factors, namely: chicken compost with 2 levels and 4 levels of biochar by testing the compost dose and the type of biochar with a dose of 15 tons ha-1. The interaction between the treatment of the effect of biochar dose (B) and the dose of chicken compost (K) had no significant effect on all observed variables. The biochar treatment had a significant to very significant effect on most of the observed variables, except for the variable number of leaves, number of fruit, dry weight of fruit oven, dry weight of streak oven, which had no significant effect, while the chicken compost treatment had a very significant effect. real for all variables. Provision of chicken biochar type increased fruit fresh weight in the treatment of chicken biochar, which was 1387.49 g which increased by 18.13% compared to treatment without biochar, which was 1135.92 g, while the fresh weight of fruit at compost dose chicken, namely 1455.13 g, increased by 30.33% compared to the treatment without compost, namely 1013.74 g Keywords: Biochar; compost; and chili plants